Body Composition Values of NCAA Division 1 Female Athletes Derived From Dual-Energy X-Ray Absorptiometry. Issue 10 (October 2021) - Dobrosielski, Devon A.; Leppert, Kyle M.; Knuth, Nick D.; Wilder, Joshua N.; Kovacs, Louis; Lisman, Peter J.
Abstract : Abstract: Dobrosielski, DA, Leppert, KM, Knuth, ND, Wilder, JN, Kovacs, L, and Lisman, PJ. Body composition values of NCAA Division 1 female athletes derived from dual-energy x-ray absorptiometry. J Strength Cond Res 35(10): 2886–2893, 2021—This study generated descriptive data for regional and total body composition and bone mineral density (BMD) measures using dual-energy x-ray absorptiometry (DXA) across 12 NCAA Division 1 female competitive sports. Two hundred seventy-eight female collegiate athletes underwent DXA: basketball (BB; n = 28), cross country ( CC = 11), field hockey (FH; n = 35), gymnastics (GYM; n = 23), lacrosse (LAX; n = 48), soccer (SOC; CC = 27), softball (SB; n = 24), swimming and diving (SW; n = 35), tennis (TN; n = 11), track and field ([TR-throw; n = 10]; [TR-run; n = 10]), and volleyball (VB; n = 16). Descriptive statistics for all body composition and BMD measures were calculated. Group mean differences in all regional and total body composition (all, p < 0.001; η 2 range = 0.177–0.365) and BMD (all, p < 0.001; η 2 range = 0.317–0.383) measures were observed between teams. The total BF% for gymnasts (23.5%) was lower than TN, FH, LAX, SB, and TR-throw (mean difference range: −4.6 to −12.9%, all p < 0.01); TR-throw had the highest total BF% (36.4%). Cross country had lower total BMD (1.17 g·cm −2 ) than FH, TR-throw, LAX, GYM, SOC, SB, VB, and BB (mean difference range: −0.12 to −0.26 g·cm −2, all p < 0.01); BB and TR-throw had the highest total BMD (1.40 and 1.43 g·cm −2, respectively). Our data confirm that regional and total body composition and BMD measures varied across female collegiate sports. These findings may assist sports medicine and strength and conditioning practitioners with identifying sport-specific goal values for BF% and BMD to optimize program design.